Fundamentals of tool design (Society of Manufacturing Engineers, 2003)
The creation of a fifth edition is proof of the continuing vitality of the book's contents, including; tool design and materials; jigs and fixtures; workholding principles; die manipulation; inspection, gaging, and tolerances; computer hardware and software and their applications; joining processes, and pressworking tool design. To stay abreast of the newer developments in design and manufacturing, every effort has been made to include thos technologies that are currently finding applications in tool engineering. For example, sections on rapid prototyping, hydroforming, and simulation have been added or enhanced. The basic principles and methods discussed in Fundamentals of Tool Design can be used by both students and professionals for designing efficient tools.